2018
DOI: 10.3390/ijerph15112480
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Assessment as an Early Biomonitor of Mercury-Induced Health Disorders in Artisanal and Small-Scale Gold Mining Areas in Indonesia

Abstract: The evaluation of mercury impact on humans is currently nonspecific because the body characteristics (homeostasis) of each human being varies. Therefore, in the early diagnosis of mercury toxicity, one of the most important monitoring parameters is the respiratory function examination. In this study, respiratory function was examined with a portable spirometer and correlated with the mercury levels in hair from the noses and heads of subjects. Samples were taken from artisanal and small-scale gold mining (ASGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Mercuric chloride (HgCl 2 ) caused an apparent increase in the levels of TNF-α, IL-1β, and IL-2, indicating the production of inflammation. Previous studies have shown that heavy metals increase IL-1β, TNF-α, and IL-2 levels in lung tissue which may be similar to those produced in COVID-19 patients [ 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 86%
“…Mercuric chloride (HgCl 2 ) caused an apparent increase in the levels of TNF-α, IL-1β, and IL-2, indicating the production of inflammation. Previous studies have shown that heavy metals increase IL-1β, TNF-α, and IL-2 levels in lung tissue which may be similar to those produced in COVID-19 patients [ 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 86%
“…Although respiratory dysfunction is known to be the characteristic feature of acute mercury (Hg) vapor inhalation ( Smiechowicz et al, 2017 ), data on the relationship between environmental Hg pollution and pulmonary function are rather insufficient. Previous studies revealed a significant inverse association between hair Hg and respiratory function in subjects from artisanal and small-scale gold mining areas ( Pateda et al, 2018 ). High serum Hg levels (third tertile) were associated with increased odds of obstructive lung disease (OR= 3.62; 95%CI: 1.29-10.18) in a dusty area ( Heo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 91%
“…Some of the health problems caused are excessive salivation, shortness of breath and fatigue, bronchitis, tremors and irritability, personality changes (due to brain damage), a sensation of floating teeth and pain in them, kidney and respiratory damage that can lead to death from problems in the lungs and other organs of the body [74][75][76]. While breathing polluted air, elemental mercury can reach the brain, affecting nerve cells and the olfactory system.…”
Section: Ames Testmentioning
confidence: 99%